H2S removal by copper enriched porous carbon cuboids. (April 2022) - Thomou, Eleni; Basina, Georgia; Spyrou, Konstantinos; Wahedi, Yasser Al; Rudolf, Petra; Gournis, Dimitrios
Highlights: Three porous structures based on carbon cuboids were synthesized. All samples showed catalytic activity towards H2 S besides acting as H2 S sorbents. H2 S conversion increased with increasing surface area. H2 S breakthrough capacity increased with increasing copper content. We observed selective oxidation of H2 S yielding elemental sulfur. Abstract: Hydrogen sulfide (H2 S) removal by adsorption from gas streams is crucial to prevent the environmental and industrial damage it causes. Amongst the nanostructures considered excellent candidates as sorbents, porous carbon has been studied extensively over the last years. In the present work we present a synthetic procedure for three high potential sorbents based on carbon cuboids, namely a low-surface-area copper-rich structure, a highly porous aggregate without metal addition, and lastly the same porous carbon decorated with copper. The properties and performance as catalysts of these three sorbents were evaluated by powder X-ray diffraction, X-ray photoelectron spectroscopy, thermal analysis, scanning electron microscopy with energy dispersive X-ray analysis, surface area determination through N2 adsorption and desorption, as well as by H2 S adsorption measurements. Graphical abstract: Image, graphical abstract